Characterisation of recombinant Trichoderma reesei cellobiohydrolase and the potential of cellulase mixture in hydrolyzing oil palm empty fruit bunches - Quay, Doris Huai Xia; Yong, Hui Yee; Rosli Md Illias; Nor Muhammad Mahadi; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Penerbit Universiti Kebangsaan Malaysia, 2017)
The potential for recombinant cellulases from fungi to hydrolyze oil palm empty fruit bunches (OPEFB) into simple sugars was investigated. A mixture of two recombinant enzymes consisting of a cellobiohydrolase from Trichoderma reesei and an endoglucanase from Aspergillus niger, was evaluated for OPEFB hydrolysis. The development of A. niger endoglucanase has been described previously. In this work, the development of a recombinant cellobiohydrolase and the activity of this enzyme mixture towards OPEFB hydrolysis were described. To obtain recombinant cellobiohydrolase, the cDNA encoding for cellobiohydrolase, cbhII, was isolated from the T. reesei strain M5, and the gene was expressed in the methylotrophic yeast, Pichia pastoris. Partially purified CbhII demonstrated optimum activity at 50°C and pH 5.0. This enzyme was shown to hydrolyze Avicel at a concentration of 0.486 U/mg under optimum conditions. Hydrolysis of pretreated OPEFB using CbhII and endoglucanase EglA showed that the total reducing sugar produced was higher in the enzyme mixture reaction than were produced in an individual enzyme reaction. Addition of β-glucosidase and an enzyme cofactor significantly increased enzyme activity and OPEFB cellulose hydrolysis. This study demonstrated the capability of an enzyme mixture to produce sugars from oil palm lignocellulosic waste.